Information systems : development, applications, education : 10th SIGSAND/PLAIS EuroSymposium 2017, Gdansk, Poland, September 22, 2017, Proceedings - Wrycza, Stanisław; Maślankowski, Jacek (Springer, 2017)
This book constitutes the refereed proceedings of the 10th SIGSAND/PLAIS EuroSymposium 2017 titled Information Systems: Research, Development, Applications, and Education, held in Gdansk and Sopot, Poland, on September 27, 2017. The objective of the EuroSymposium on Systems Analysis and Design is to promote and develop high quality research on all issues related to analysis and design (SAND). It provides a forum for SAND researchers and practitioners in Europe and beyond to interact, collaborate, and develop their field. The 10 papers presented in this volume were carefully reviewed and selected from 45 submissions. They are organized in topical sections on data analytics, Web-based information systems, and information systems development.
Keywords: System analysis -- Congresses.; System design -- Congresses.; elektronické knihy; electronic books